2013
DOI: 10.7287/peerj.preprints.82v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The geographic scaling of biotic interactions

Abstract: A central tenet of ecology and biogeography is that the broad outlines of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
209
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(229 citation statements)
references
References 1 publication
11
209
1
8
Order By: Relevance
“…First, ignoring large‐scale factors, such as climate gradients, dispersal barriers, historical contingencies and evolutionary history, can mask the outcomes of small‐scale processes, such as local abiotic filters and competition (Cardinale et al, 2013; Cavender‐Bares, Keen, & Miles, 2006; Swenson, Enquist, Pither, Thompson, & Zimmerman, 2006; Vamosi et al, 2009). Second, ignoring small‐scale factors, such as intraspecific variation in trait values (Albert et al, 2012; Siefert et al, 2015) and the fine‐scale spatial arrangement of individuals (Diekmann, Law & Metz, 2000), can lead to the underlying processes being overlooked because their effects may not scale up to large‐scale diversity patterns (Araujo & Rozenfeld, 2014; Thuiller et al, 2010; Turcotte & Levine, 2016). For example, it has been shown that trait plasticity increases niche differences in communities and thereby stabilizes coexistence and promotes diversity (Pérez‐Ramos, Matías, Gómez‐Aparicio, & Godoy, 2019).…”
Section: Common Pitfallsmentioning
confidence: 99%
“…First, ignoring large‐scale factors, such as climate gradients, dispersal barriers, historical contingencies and evolutionary history, can mask the outcomes of small‐scale processes, such as local abiotic filters and competition (Cardinale et al, 2013; Cavender‐Bares, Keen, & Miles, 2006; Swenson, Enquist, Pither, Thompson, & Zimmerman, 2006; Vamosi et al, 2009). Second, ignoring small‐scale factors, such as intraspecific variation in trait values (Albert et al, 2012; Siefert et al, 2015) and the fine‐scale spatial arrangement of individuals (Diekmann, Law & Metz, 2000), can lead to the underlying processes being overlooked because their effects may not scale up to large‐scale diversity patterns (Araujo & Rozenfeld, 2014; Thuiller et al, 2010; Turcotte & Levine, 2016). For example, it has been shown that trait plasticity increases niche differences in communities and thereby stabilizes coexistence and promotes diversity (Pérez‐Ramos, Matías, Gómez‐Aparicio, & Godoy, 2019).…”
Section: Common Pitfallsmentioning
confidence: 99%
“…Conducting such investigations can help to detect robust patterns and processes that transcend taxonomic and geographic boundaries (Brown, 1999), and help to control for potential biases occurring from studying too few species or spatial scales that are too small (Hulme et al, 2013). Despite the vast number of smaller-scale investigations on biological invasions, these studies cannot provide comprehensive insight into the complexities of invasions at macroscales (Pauchard & Shea, 2006), as data required to do so need to be collected across multiple geographic scales (Ara ujo & Rozenfeld, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While it is a tenet that climate would shape the geographical distribution of biodiversity, an increasing number of studies have showed that biotic interactions also play important roles in limiting species distribution (Araújo & Rozenfeld, 2014;Kissling & Schleuning, 2015;Wisz et al, 2013).For example, global mammal predator richness is more associated with prey species richness than productivity, climate, and human influence (Sandom et al, 2013). Herbivore diversity in the Arctic is positively related with species richness of predators (Barrio et al, 2016).…”
Section: Biotic Interactions and Geographical Distribution Of Mammamentioning
confidence: 99%